Global trajectories, dynamics, and tendencies of business software piracy: benchmarking IPRs harmonization - Simplice A. Asongu; Andrés Antonio (African Governance and Development Institute (AGDI), 2014)
In this paper, we examine global trajectories, dynamics, and tendencies of software piracy to ease the benchmarking of current efforts towards harmonizing the standards and enforcements of Intellectual Property Rights (henceforth IPRs) protection worldwide. Our empirical exercise is based on 15 different panel regressions, which together consists of 99 countries. The richness of the dataset allows us to disaggregate countries into fundamental characteristics of business software piracy based on income-levels (high-income, lower-middle-income, upper-middle-income and low-income), legal-origins (English common-law, French civil-law, German civil-law and, Scandinavian civil-law) and, regional proximity (South Asia, Europe & Central Asia, East Asia & the Pacific, Middle East & North Africa, Latin America & the Caribbean and, Sub-Saharan Africa). Our main finding suggest that, a genuine timeframe for standardizing IPRs laws in the fight against software piracy is most feasible within a horizon of 4.3 to 10.4 years. In other words, full (100%) convergence within the specified timeframe will mean the enforcements of IPRs regimes without distinction of nationality or locality within identified fundamental characteristics of software piracy. The absence of convergence (in absolute and conditional terms) for the World panel indicates that, blanket policies may not be effective unless they are contingent on the prevailing trajectories, dynamics and tendencies of software piracy. Policy implications and caveats are also discussed.
Keywords: F42; K42; O34; O38; O57; 330; Piracy; Business Software; Software piracy; Intellectual Property Rights; Panel data; Convergence